Porin threading drives receptor disengagement and establishes active colicin transport through Escherichia coli OmpF - Francis, M-LR; Webby, MN; Housden, NG; Kaminska, R; Elliston, E; Chinthammit, B; Lukoyanova, N; Kleanthous, C (EMBO Press, 2021)
Bacteria deploy weapons to kill their neighbours during competition for resources and to aid survival within microbiomes. Colicins were the first such antibacterial system identified, yet how these bacteriocins cross the outer membrane (OM) of Escherichia coli is unknown. Here, by solving the structures of translocation intermediates via cryo-EM and by imaging toxin import, we uncover the mechanism by which the Tol-dependent nuclease colicin E9 (ColE9) crosses the bacterial OM. We show that threading of ColE9's disordered N-terminal domain through two pores of the trimeric porin OmpF causes the colicin to disengage from its primary receptor, BtuB, and reorganises the translocon either side of the membrane. Subsequent import of ColE9 through the lumen of a single OmpF subunit is driven by the proton-motive force, which is delivered by the TolQ-TolR-TolA-TolB assembly. Our study answers longstanding questions, such as why OmpF is a better translocator than OmpC, and reconciles the mechanisms by which both Tol- and Ton-dependent bacteriocins cross the bacterial outer membrane.